(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The term "blended learning" described by domestic and foreign scientists is considered in the article. A number of advantages of blended learning have been marked out in comparison with traditional one: flexibility, learning personification, increase of motivation of students to training,variety of forms of arrangement of educational process and forms of presentation of teaching material and increase of efficiency of activity of the teacher. A set of key competencies a teacher should possess to support effective activity in the mixed educational environment has been analyzed. The scientists of the Learning Accelerator organization engaged in support of introduction of blended learning in American schools presented it. It is determined that its main difference from a teacher who uses traditional methods and training forms – desire to experiment,introducing various innovative pedagogical technologies in educational process to achieve maximum result. There is also a desire to create favorable conditions for successful learning of each student considering strong and weak sides. The scientists of Clayton Christensen Institute designed the models of organization of blended learning. These models were analyzed. Two expedient models for implementation in higher school, in particular, in preparation of future teachers of informatics have been defined: station rotation and "flipped classroom".